2022
DOI: 10.24925/turjaf.v10i12.2438-2445.5477
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Recent Remote Sensing Data Using an Artificial Neural Network to Predict Soil Moisture by Focusing on Radiometric Indices

Abstract: Remote sensing data is widely used as a common variable for digital soil mapping estimating models. The aim of this study, quite recently made available to researchers Operational Land Imager 2 (OLI–2) have structure Landsat 9 and Landsat 8 (OLI) and Sentinel 2A (MSI) to compare the performance of soil moisture estimation in multi-layer perceptron network (MLP) artificial intelligence algorithm of image data. The working area is 886.78 km2 and soil sampling was performed at 66 points for gravimetric soil moist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…The study, recently conducted in Indonesia, provided strong evidence to support the possibility of deriving soil moisture content from spatial NDMI values using a linear regression function with the average error of less than 5% and 94.6% linearity (Cahyono et al, 2022). Another scientific evidence in support of the possibility of estimating soil moisture content using NDMI values was provided by Kılıç & Gündoğan (2022), who found that NDMI had a moderately significant positive correlation with soil moisture content, identified by the gravimetric method. Considering the claims mentioned above and the results of the current study, there is evidence in support of the implementation of remote sensing NDMI in soil moisture monitoring both in irrigated and non-irrigated conditions.…”
Section: Tablementioning
confidence: 85%
“…The study, recently conducted in Indonesia, provided strong evidence to support the possibility of deriving soil moisture content from spatial NDMI values using a linear regression function with the average error of less than 5% and 94.6% linearity (Cahyono et al, 2022). Another scientific evidence in support of the possibility of estimating soil moisture content using NDMI values was provided by Kılıç & Gündoğan (2022), who found that NDMI had a moderately significant positive correlation with soil moisture content, identified by the gravimetric method. Considering the claims mentioned above and the results of the current study, there is evidence in support of the implementation of remote sensing NDMI in soil moisture monitoring both in irrigated and non-irrigated conditions.…”
Section: Tablementioning
confidence: 85%